Effects of Viewing Cute Pictures on Quiet Eye Duration and Fine Motor Task Performance - Yoshikawa, Naoki; Nittono, Hiroshi; Masaki, Hiroaki (Frontiers in Psychology, 2020)
We investigated if viewing cute pictures could improve fine motor skills and prolong quiet eye (QE) duration in a high-pressure situation. QE is a gaze phenomenon, and its duration (i.e., the period between fixation onset preceding a critical movement and fixation offset) is thought to represent attention control. As it has been reported that QE duration is longer for expert athletes than for novice athletes in various sports, and becomes shorter even for experts who choke under pressure during games, resulting in performance deterioration, QE prolongation is important to prevent choking under pressure. Separately, several studies have confirmed that viewing cute pictures can induce focal attention, thus improving performance in fine motor tasks. We hypothesized that viewing cute pictures may modulate attention control and prolong QE duration. We tested if the beneficial effects of viewing cute pictures could be obtained in a high-pressure situation in which participant performance was evaluated by an experimenter. We used a fine-motor task requiring participants to use a pair of tweezers to remove 12 small pieces from holes in a game board. We randomly assigned participants to either the baby-animal pictures group or the adult-animal pictures group, based on pictures viewed prior to the task. Participants executed the task in a pre-test, post-test, and pressure test. In both the post-test and the pressure test, participants viewed seven photographs of either baby animals or adult animals before execution of the task. In accordance with previous research, task precision increased after viewing pictures of baby animals in both the post-test and pressure test. Furthermore, QE duration was also prolonged after viewing cute pictures in the post-test, but not in the pressure test. Neither performance improvement nor QE prolongation were found after viewing pictures of adult animals. These results suggested that simply viewing cute pictures could prolong QE duration without pressure, and might provide a beneficial effect on performance, even in a high-pressure situation.